Parcel locker solutions for last mile delivery: a systematic literature review and future research directions - Zhang, Qiruo; Demir, Emrah (Frontiers in Future Transportation, 2025)
The rapid growth of online shopping has increased customer demand for efficient logistics and last mile delivery. Parcel lockers (PLs) offer a promising solution by integrating digital technology with secure parcel handling, reducing delivery bottlenecks and traffic congestion while optimizing personnel utilization and improving efficiency. We conduct a systematic review of the literature on PL research, with a particular focus on its impact on cost reduction, operational efficiency, and sustainability. Most existing research on PL networks is heavily concentrated on determining optimal locations and developing efficient routing strategies. That said, some scholars have also explored other operational challenges, such as incorporating dynamic factors and diverse delivery capabilities into PL systems. This study identifies research gaps, such as the lack of empirical studies on mobile PLs and their integration with other urban logistics systems, and offers directions for future research. These findings contribute to understanding the potential of PL systems in advancing more efficient and sustainable last mile delivery solutions.